The Effect of the Dimensions of Transformational Leadership on the Teachers' Performance in the Yemeni Public Schools - Mohammed Alzoraiki; Othman bin Ab. Rahman; Mahazan Abdul Mutalib (European Scientific Journal, ESJ, 2018)
The aim of this study is to determine the dimensions of transformational leadership that influence schools to achieve productivity growth and improve the performance of teaching as well as gaining access to new high-quality education. Although schools have been competing to gain high-quality education, empirical evidence shown that many educational processes with regards to teaching performance were not successful particularly in Yemen. Consequently, the study is often concentrated on identifying the paths to enhance teaching performances. The most important factor to successfully increase high-quality education is providing appropriate transformational leadership during the process of reform, particularly in the important period of the teaching process. In order to accept changes and focus on attaining ambitious goals, it is necessary for leaders of transformational school to provide rewards and support the teachers. This paper aimed to investigate the influence of various dimensions of transformational leadership on performance of teachers in Yemeni public schools. In order to guarantee the sample’s representativeness, the questionnaires have been distributed to Yemeni public schools in Sana'a, Republic of Yemen. A total of 374 respondents were selected which include staff and teachers as the sample. The instrument used was a Likert 5-point scale from the questionnaire which were examined using smartpls3. The results revealed that all the dimensions of transformational leadership have a positive influence on the teachers' performance.